PENINGKATAN PEMANFAATAN LITERASI DIGITAL DI KALANGAN IBU RUMAH TANGGA YANG TIDAK BEKERJA DI LINGKUNGAN DESA WATUBELAH, KABUPATEN CIREBON - Iin Indrayanti; Ahmad Ramdhani; Syaefani Arif Romadhon (Universitas Muhammadiyah Tapanuli Selatan, 2022)
Stereotypes about domestic routines in the kitchen, wells, and mattresses are strongly associated with married women. This has been occurred for long time. Nowadays, technological advancement and developing digital capabilities are essential not only among students and blue-collars, but also housewives. Since most individual own a smartphone or tablet, he or she should be able to use the technology and continue improving their digital literacy. However, among housewives, its use and utilization are still limited to entertainment, socializing, and making friends in social media. This time, Community Service Program (PKM) activities led to the formation of counseling and education about the importance of increasing digital literacy with the purpose of improving digital literacy skills and the use of Android-based English learning apps. This activity involved approximately 50 housewives as parents and their children from PAUD Alam Nur Cendekia. The session began with a description of the importance of continuing to improve literacy skills, which was preceded by an introduction of using Google Forms to write and share ideas or daily experiences through the links provided. In addition, the mothers were shown how to install, explore, and practice using an android-based English learning application called ENGLISH FOR KIDS. As a result, this can facilitate their children in learning English in a more entertaining way. Subjects participated in the session with enthusiasm and passion. This shows that the implementation of Community Service Program (PKM) ran smoothly in accordance with the above aim.